2023
DOI: 10.1073/pnas.2212694120
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function correlates of fibrinogen binding by Acinetobacter adhesins critical in catheter-associated urinary tract infections

Abstract: Multidrug-resistant  Acinetobacter baumannii infections are an urgent clinical problem and can cause difficult-to-treat nosocomial infections. During such infections, like catheter-associated urinary tract infections (CAUTI), A. baumannii rely on adhesive, extracellular fibers, called chaperone-usher pathway (CUP) pili for critical binding interactions. The A. baumannii uropathogenic strain, UPAB1, and the pan-European subclone II isolate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…While the two adhesins share a great deal of structural similarly, the anterior loop of the binding pocket is considerably more flexible in Abp1DRBD than in Abp2DRBD. 25 Because of this flexibility Abp1DRBD can adopt either a "closed" (lower affinity) or "open" (higher affinity)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the two adhesins share a great deal of structural similarly, the anterior loop of the binding pocket is considerably more flexible in Abp1DRBD than in Abp2DRBD. 25 Because of this flexibility Abp1DRBD can adopt either a "closed" (lower affinity) or "open" (higher affinity)…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] Our recent studies of A. baumannii CAUTI pathogenesis have revealed that A. baumannii CUP adhesins are critical in catheter colonization and thus may represent promising drug targets. 8,25 When a urinary catheter is inserted into the bladder, it induces inflammation and leads to deposition of host proteins, such as fibrinogen, onto the surface of the implant. 23,24,[26][27][28] A. baumannii have evolved two CUP pili, Abp1 and Abp2, tipped with fibrinogen binding adhesins Abp1D and Abp2D respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study found that inhibition of mitochondrial DNA translation was a potential molecular mechanism [31] . A study found that Multidrugresistant Acinetobacter baumannii can bind brinogen, through two domain tip adhesins, Abp1D and Abp2D, respectively [32] .Plasminogen bound to CipA, which mediates complement resistance of Acinetobacter baumannii, could be activated to plasmin to degradation brinogen [33] . This may explain that there were no differences in APTT and PT.…”
Section: Discussionmentioning
confidence: 99%
“…It included assemblies of over 300,000 genomes which had not previously been available (the raw data only had been available). The assemblies and search indexes allowed multiple other studies of plasmids[5, 6], bacterial adaptation[7, 8, 9, 10], and compression/indexing algorithms[11, 12, 13, 14, 15]. However, there were a few limitations.…”
Section: Introductionmentioning
confidence: 99%